Does thiamine protect the brain from iron overload and alcohol‐related dementia?. Issue 11 (18th August 2020) - Listabarth, Stephan; König, Daniel; Vyssoki, Benjamin; Hametner, Simon
Abstract: Alcohol‐related dementia (ARD) is a common and severe co‐morbidity in alcohol use disorder (AUD). We propose brain iron overload (BIO) to be an important and previously neglected pathogenic process, accelerating cognitive decline in AUD. Furthermore, we suggest thiamine, which is frequently depleted in AUD, to be a key modulator in this process: Thiamine deficiency impairs the integrity of the blood‐brain barrier, thereby enabling iron to pass through and accumulate in the brain. This hypothesis is based on findings from animal, translational, and neuroimaging studies, discussed in this article. To validate this hypothesis, translational studies focusing on brain iron homeostasis in AUD, as well as prospective clinical studies investigating prevalence and clinical impact of BIO in AUD, should be conducted. If proven right, this would change the understanding of ARD and may lead to novel therapeutic interventions in prevention and treatment of ARD.